Murine HSCs contribute actively to native hematopoiesis but with reduced differentiation capacity upon aging - Säwen, Petter; Eldeeb, Mohamed; Erlandsson, Eva; Kristiansen, Trine A; Laterza, Cecilia; Kokaia, Zaal; Karlsson, Göran; Yuan, Joan; Soneji, Shamit; Mandal, Pankaj K; Rossi, Derrick J; Bryder, David (eLife, 2018)
A hallmark of adult hematopoiesis is the continuous replacement of blood cells with limited lifespans. While active hematopoietic stem cell (HSC) contribution to multilineage hematopoiesis is the foundation of clinical HSC transplantation, recent reports have questioned the physiological contribution of HSCs to normal/steady-state adult hematopoiesis. Here, we use inducible lineage tracing from genetically marked adult HSCs and reveal robust HSC-derived multilineage hematopoiesis. This commences via defined progenitor cells, but varies substantially in between different hematopoietic lineages. By contrast, adult HSC contribution to hematopoietic cells with proposed fetal origins is neglible. Finally, we establish that the HSC contribution to multilineage hematopoiesis declines with increasing age. Therefore, while HSCs are active contributors to native adult hematopoiesis, it appears that the numerical increase of HSCs is a physiologically relevant compensatory mechanism to account for their reduced differentiation capacity with age.
Keywords: hematopoiesis; stem cells; steady state; aging; lineage tracing